Psychological Factors related to traffic accidents - Serafín Aldea Muñoz (Revista Internacional de Psicología, 2002)
Automobile drivers fine themselves affected by series psychological factors which are directly related to traffic accidents. In this study we intend to investigate these variables, basing our work on the most convenient sources of information, coming from the police, the General Direction of Traffic, the courts, insurance companies, the Red Cross, Social Security, and forensics.